(untitled) (African Journal of Biomedical Research, 2021)
Self-microemulsifying drug delivery system (SMEDDS) is one approach for improving solubility and consequently the oral bioavailability of class 2 drugs in the biopharmaceutical classification system such as diclofenac which have low aqueous solubility but high lipid permeability. The aim of this study was to formulate self-microemulsifying drug delivery system based on coconut oil for the delivery of diclofenac, a hydrophobic non-steroidal anti-inflammatory drug (NSAID). Coconut oil was extracted and used in combination with tween 80, polyethylene glycol 400 (PEG400) and propylene glycol at varying ratios for the formulation of diclofenac-loaded solid self-microemulsifying drug delivery system (DCF-loaded solid SMEDDS) which were encapsulated in hard gelatin capsules and evaluated for drug content, emulsification time and in vitro drug release. The results from the study revealed that over 80 % of diclofenac was released from the SMEDDS within 30 minutes and percentage drug content was above 90 % except for BF3, BF5, and BF6 which were 87 %. Emulsification time for all the batches except BF6 were within 120 sec (2 min). It can be concluded that coconut oil in combination with polyethylene glycol 400 (PEG-400) and tween 80 could be used in the formulation of SMEDDS for the delivery of diclofenac for dissolution enhancement.